Detailed XPS analysis and anomalous variation of chemical state for Mn- and V-doped TiO2 coated on magnetic particles. Issue 18 (15th December 2017) - Chen, Zheng; Zhao, Yisen; Ma, Junqiang; Liu, Chang; Ma, Yongqing
Abstract: Manganese (Mn)- and vanadium (V)-doped titania (TiO2 ) coated on iron oxide (γ-Fe2 O3 ) nanoparticles (TM and TV) were reduced in H2 /N2 mixture atmospheres at different reducing temperatures T R . Furthermore, TM and TV reduced at T R = 800 °C (TM8 and TV8) were subsequently nitrided in the ammonia (NH3 ) atmosphere at different temperatures T N in order to change the chemical state (CS) of the Mn, V, Fe, Ti, O, and N elements. Samples were characterized by X-ray diffraction and X-ray photoelectron spectroscopy. For reduced samples, with increasing T R, anomalous variation of CS is as follows: Ratios of V 4+ and V 5+ increased, while the ratio of V 3+ decreased, and the ratio of oxygen vacancy O v decreased. Data conflict with the effect of reduction reaction could be understood as follows: O v was occupied by O from H2 O (product of the reduction reaction), according to previous theoretical result. For nitrided samples, compared to TM8 and TV8 samples, as T N increased, ratios of Mn 4+ and V 5+ with the highest valence state exhibited an increase at T N = 400 °C. Moreover, the ratio of TiOx decreased and the ratio of TiO2 increased, even though NH3 exhibited good reducibility. Data could be well interpreted as follows: O v was occupied by N along with adsorbed O, possibly in the form of neutral NO radical and NO2 2− radical ion. Till date, these phenomena have not been reported experimentally, which are important to understand the mechanism for photocatalytic performance of Mn-, V-, N-, and self-doped TiO2 . Highlights: The anomalous chemical states of Mn, V and O were observed. The reduction enhances both the photocatalytic activity and magnetization. The appropriate nitridation can further improve the photocatalytic activity. The optimal nitriding temperature is obtained to be 500 °C.